“It’s just another tool on my toolbelt”: New York state law enforcement officer experiences administering naloxone - Danielle Lloyd; Kirsten Rowe; Shu-Yin John Leung; Elham Pourtaher; Kitty Gelberg (Harm Reduction Journal, 2023)
Abstract Background Although naloxone is widely acknowledged as a life-saving intervention and a critical tool for first responders, there remains a need to explore how law enforcement officers have adapted to a shifting scope of work. Past research has focused mainly on officer training, their abilities to administer naloxone, and to a lesser extent on their experiences and interactions working with people who use drugs (PWUD). Methods A qualitative approach was used to explore officer perspectives and behaviors surrounding responses to incidents of suspected opioid overdose. Between the months of March and September 2017, semi-structured interviews were conducted with 38 officers from 17 counties across New York state (NYS). Results Analysis of in-depth interviews revealed that officers generally considered the additional responsibility of administering naloxone to have become “part of the job”. Many officers reported feeling as though they are expected to wear multiple hats, functioning as both law enforcement and medical personnel and at times juggling contradictory roles. Evolving views on drugs and drug use defined many interviews, as well as the recognition that a punitive approach to working with PWUD is not the solution, emphasizing the need for cohesive, community-wide support strategies. Notable differences in attitudes toward PWUD appeared to be influenced by an officer’s connection to someone who uses drugs and/or due to a background in emergency medical services. Conclusion Law enforcement officers in NYS are emerging as an integral part of the continuum of care for PWUD. Our findings are capturing a time of transition as more traditional approaches to law enforcement appear to be shifting toward those prioritizing prevention and diversion. Widespread adoption of naloxone administration by law enforcement officers in NYS is a powerful example of the successful integration of a public health intervention into police work.